2019
DOI: 10.4038/jnsfsr.v47i4.9687
|View full text |Cite
|
Sign up to set email alerts
|

Silver montmorillonite conducting polymer composite materials as low-cost oxygen reduction catalysts

Abstract: Throughout the globe, researchers are in quest of electro-catalysts for oxygen reduction reaction (ORR) in order to develop cathode materials for fuel cells (FCs). Although the anodic half-reactions of FCs are fast enough for oxidation of any fuel on cheap catalysts, ORR at the cathode is a slow process even with expensive platinum-based catalysts. Development of low-cost electro-catalysts with reasonably fast kinetics for (ORR) is desirable if fuel cell power is to be utilised in practice. The present study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Figure 1 There are a handful of studies that investigated the utility of clays as support for ORR electrocatalysts [12][13][14][15][16][17]. These studies showed that the ORR peak for such materials are positioned at approximately -0.4 V [16,17,21]. Furthermore, this cathodic peak cannot be attributed to the reduction of the conductive polymer since PANI in this study was degraded during pyrolysis.…”
Section: Cyclic Voltammetry (Cv) Studiesmentioning
confidence: 85%
See 4 more Smart Citations
“…Figure 1 There are a handful of studies that investigated the utility of clays as support for ORR electrocatalysts [12][13][14][15][16][17]. These studies showed that the ORR peak for such materials are positioned at approximately -0.4 V [16,17,21]. Furthermore, this cathodic peak cannot be attributed to the reduction of the conductive polymer since PANI in this study was degraded during pyrolysis.…”
Section: Cyclic Voltammetry (Cv) Studiesmentioning
confidence: 85%
“…In an alkaline environment, the direct ORR involving 4e-produces hydroxides (OH-) which is an intermediate of the reaction [20]. According to Senarathna and Rajapakse [17], ORR occurs more suitably in alkaline media, with metals such as Fe and Co able to aid in the degradation of hydroxide ions. This situation makes the ORR potential close in value to the theoretical oxygen electrode potential [17].…”
Section: Cyclic Voltammetry (Cv) Studiesmentioning
confidence: 99%
See 3 more Smart Citations